Dynamic Tourism in ASEAN Countries: Do Institutional Indicators Matter? - Sari, Vita Kartika; Cahyadin, Malik (Jurnal Ekonomi & Studi Pembangunan, 2021)
Tourism is one of the fastest-growing industries. Tourism is able to move the economy forward at the micro-level such as encouraging the informal sector and local potential while at the macro level it can increase currency transactions. In various countries, the tourism sector is able to increase domestic and foreign demands as well as to encourage transportation, hospitality, and manufacturing industries. This study examines the effect of institutional indicators on tourism in ASEAN countries during 2000-2018 under dynamic panel estimation. The number of observations was about 180, namely: time series from 2000-2018 and cross-section of 10 countries. ASEAN as one of the destinations in the world requires an increase in institutional quality to be able to compete and provide world-class tourism services. The six institutional indicators were employed such as voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption. Moreover, the dynamic panel estimation was expressed by Pooled OLS and REM estimations. Interestingly, the findings show that political stability compromises the number of tourist arrivals while government effectiveness can stimulate tourist arrivals. Similarly, GDP per capita can hinder the number of tourist arrivals, while the exchange rate leads increasing of tourism arrivals. Thus, the governments in ASEAN countries can promote and cooperate together to develop tourism in the regional level. The GDP per capita of ASEAN countries should be increased, and the level of exchange rate can be maintained at a stable range. Besides, the governments should also improve the quality of institutions.